HUBUNGAN PENGETAHUAN GIZI IBU, TINGKAT KONSUMSI GIZI, STATUS KETAHANAN PANGAN KELUARGA DENGAN BALITA STUNTING (Studi pada Balita Usia 24-59 Bulan di Wilayah Kerja Puskesmas Duren Kabupaten Semarang) - Fariza Aqmar Adelia; Laksmi Widajanti; Sri Achadi Nugraheni (Jurnal Kesehatan Masyarakat (Undip), 2018)
Stunting is the chronic condition that describes inhibition due to long-term malnutrition which is indicated by the score value of z-score TB/U less than -2SD. The prevalence of stunting children under five years old in Indonesia is still high, threshold value 20%. The aim of this study is to determine the correlation of mothers’ knowledge of nutrition and household food security status in stunting children under five years old. The research method of this study is observational analaytic studies and using case-control method which is conducted in Puskesmas Duren, Semarang Regency. The sample of this study is 70 chlidren under five years old which is consist of 35 stunting children and 35 normal children under five years old. Taking sample of this study, the researcher using purposive sampling technique by matching variables of age and sex children. In collecting the data, the researcher interviewing directly using questionnaire and analyzing using Chi Square with significance level of p<0,05. This study reveals that variables which has significant relation with stunting children under five years old and a risk factors is the lack of mothers’ knowledge of nutrition (p = 0,017; OR = 3,962), lack of energy intake (p = 0,000; OR = 12,083), and low household food security (p = 0,049; r = 3,059). There is no correlation between lack of protein intake with stunting in children under five years old (p = 0.078, OR = 2,842). This study suggest the mothers to pay more attention to the needs of children’s nutrition especially energy needs, more active looking for information the growth of children and monitoring children growth by measuring their heights regulary.